Forensic Palynological Analysis of Intestinal Contents of a Korean Mummy. Issue 6 (June 2015) - Arguelles, Paulette; Reinhard, Karl; Shin, Dong Hoon
ABSTRACT Experimental studies show that pollen resides in the intestinal tract for a minimum of seven days to at least 21 days. Because of this long residence time, pollen analysis is an important avenue of forensic research. Pollen provides evidence of the environment of the decedent as well as foods and medicine. We analyzed a coprolite recovered from a Korean mummy. The decedent was a high‐ranking general who lived during the 16th or17th centuries. Twenty pollen types were recovered. These ranged from 100s to 10, 000s of pollen grains per gram of coprolite. Importantly, comparison of the coprolite pollen spectrum to modern aeropalynology studies of Korea suggests that the general died in winter between middle November to late February. Economic pollen types were most abundant. Economic refers to dietary, medicinal, spice, and beverage types. Dietary pollen types include pollen from Oryza (rice), Eriogonum (buckwheat), Brassicaceae (mustard family), and Solanaceae (tomato‐chile pepper family). Pollen consistent with dandelion is present and may represent its use as food. Tens of thousands of grains from water plants, bur‐reed or cattail, dominate the pollen spectrum. We believe that this was introduced with water. The large numbers of water‐related pollen suggest that the general consumed broth, tea, or soup for a considerable time before death. Anat Rec, 298:1182–1190, 2015. © 2015 Wiley Periodicals, Inc.